5x-3=-3x+35

Simple and best practice solution for 5x-3=-3x+35 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3=-3x+35 equation:


Simplifying
5x + -3 = -3x + 35

Reorder the terms:
-3 + 5x = -3x + 35

Reorder the terms:
-3 + 5x = 35 + -3x

Solving
-3 + 5x = 35 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-3 + 5x + 3x = 35 + -3x + 3x

Combine like terms: 5x + 3x = 8x
-3 + 8x = 35 + -3x + 3x

Combine like terms: -3x + 3x = 0
-3 + 8x = 35 + 0
-3 + 8x = 35

Add '3' to each side of the equation.
-3 + 3 + 8x = 35 + 3

Combine like terms: -3 + 3 = 0
0 + 8x = 35 + 3
8x = 35 + 3

Combine like terms: 35 + 3 = 38
8x = 38

Divide each side by '8'.
x = 4.75

Simplifying
x = 4.75

See similar equations:

| 13=8-x+x | | 2x^3/3y^3/2x/y | | 23x-8=128 | | 5x+4=-14y | | y=2.7x-3.6 | | 15x=33 | | 2x+3y(x)+8=36 | | 0=-16t^2+128t+90 | | 0=-16t^2+128+90 | | -4(5n+5)+4n= | | X^2+630x-3125=0 | | 22m=6 | | 16y=20-2x | | e^6x-2e^3x-3x=0 | | y+218=6y+8 | | 5x+18=96 | | b+315=-6b+7 | | (5x+6)+(3x+23)=(9x+12) | | 180-x-(x+10)-(3x-5)=0 | | (x(X-9)(5x-18)^2)/3 | | X-5+10=25 | | 9x+36-34= | | (A^4/b^2c)^5 | | (5x+6)+(3x+23)+(9x+12)=180 | | y=10-10x | | 5x+6+3x+23+9x+12=180 | | 2x+-8y=20 | | 20-4x=7x+53 | | X=50+-4x | | x-.1x=761.20 | | -.428571(m+5)=3+2m | | 112=(4b+8) |

Equations solver categories